Efektivitas Metode Storytelling Menggunakan Media Digital terhadap Kemampuan Bercerita Anak Usia 5-6 Tahun di Taman Kanak-kanak Pembagunan Laboratorium Universitas Negri Padang - Sari, Rati Ratna; Wirman, Asdi (Darul Yasin Al Sys, 2024)
The ability to tell stories is important to develop when children are at an early age. Based on observations at the UNP Development Laboratory Kindergarten, it appears that children's storytelling abilities are not yet optimal. This is due to the use of media which is still less supportive and less varied. The media used by educators still uses conventional media such as story books and picture series. One of the relevant ones is Microsoft's digital media sway. This media is able to attract children's attention and also makes it easier to listen to the stories displayed. This research aims to find out how effective digital media is in improving the storytelling abilities of young children in the UNP Laboratory Development Kindergarten. This type of research uses a quantitative approach with a Quasi Experimental method. This research was carried out in two classes, namely group B1 as an experimental class with 13 children and group B2 as a control class with 13 children. The data collection technique involves testing with 4 statement items and data analysis methods include normality tests, homogeneity tests, hypothesis tests and using effect size calculations. Based on data analysis, overall there was an increase in scores for the control and experimental classes. The pre-test score was 148 and the post-test score was 204, while the average pre-test and post-test results for the control class were 11.38 and 15.69. Meanwhile the scores on the pre-test and post-test for the experimental class were 203 and 241, with an average pre-test result of 15.62 and post-test 18.54. The resulting data is normally distributed and homogeneous. Obtaining an effect size of 1.69, it was concluded that it was included in the strong category. With this method, digital media has a significant effect on the storytelling ability of children aged 5-6 years.